Fissures of traditional culture in the novel 'Shadow partisan' by Nađa Tešić - Matić Aleksandra D. (Baština, 2024)
The paper deals with representations of traditional culture and their fissures in Nađe Tešić's novel Shadow Partisan. The tangle of cultural symbolism, socio-historical dynamics and psychological dimensions shown in the novel is considered in an interdisciplinary key, through literary, cultural and ethnological-anthological readings. The goal of the research is to shed light on the influence of traditional culture patterns on the development of characters and the constitution of the story, as well as to look at the narrative processes that manifest the heroine's rebellion against traditional norms. The first part of the paper provides a theoretical framework for the study of traditional culture patterns and their influence on the constitution of the world of literary works. By the aspects of traditional culture in the novel we mean religious and spiritual practices, ritual-ordinary complexes, everyday rituals (such as culinary ones), folk medicine and folklore, oral folklore, legends and traditions, but also power relations and gender roles. The work also explores the complex interweaving of elements of traditional culture with the intimate world of the protagonist's upbringing. With regard to the genre determination - bildungsroman, the work also examines the social dynamics within the novel, clarifying how traditional culture provides a cultural framework for understanding the identity of the community to which the main character originally belongs. We come to the conclusion that in the novel the fissures of traditional culture and through them identity, spirituality and all the value-normative creations of the world of the novel are revealed narratively.